Virtual Hajj (V-Hajj): A Persuasive Hajj Learning Procedures Courseware - Mohd Fitri, Yusoff (2012)
This study focuses on an attempt to develop a supplementary learning material for the procedures to perform the Hajj. From the preliminary studies, the existing supplementary materials and learning methods were found to be less effective in giving a clear understanding to the users, whether they are youngsters or elders. Moreover, most of the current supplementary materials are based on passive learning mode. To provide a better supplementary learning material which supports active learning and self-directed learning, this study incorporates virtual environments (VE) and Multimedia (MM) technologies to develop Virtual Hajj (V-Hajj) prototype. Certain persuasive design guidelines were also adapted to persuade users particularly the elders to change their view in using computer-based material. By employing certain important elements, a conceptual model of persuasive Hajj learning environment was constructed. It consists of MM learning principle, Cognitive Theory of MM Learning, VE constructivist theory, persuasive technology principles, MM authoring processes, VE authoring processes and persuasive design guidelines. The model and its courseware prototype are the major contributions of this study. The methodology used in this study is an adaptation of the research design used by Vaishnavi and Kuechler in 2008. It combines the processes and methods used for VE authoring and MM authoring to produce V-Hajj prototype. The expert evaluation revealed some limitations of the prototype and the limitations have been fixed. Meanwhile, the user evaluation results revealed that the V-Hajj prototype provided good indication of the applicability and usability as well as the persuasive effect of the V-Hajj prototype as a supplementary Hajj learning material to the users. In conclusion, an integration of multimedia, virtual environment and persuasive technology in designing and developing a supplementary Hajj learning material has helped users to learn better. However, certain limitations do remain, such as the number of respondents involved in this study. This will be rectified in the future.